EFFECTS OF RHIZOSPHERE AND NODULE BACTERIA OF LEGUMINOUS WEEDS ON YIELD OF MUNGBEAN GROWN FOLLOWING PADDY RICE - Muslim, Galang; Wangiyana, Wayan; Nufus, Novita Hidayatun (Jurnal Silva Samalas, 2026)
This study aimed to examine the effect of rhizosphere and root nodule bacteria isolated from several leguminous weed species on growth and yield of mungbean grown following paddy rice. The experiment was conducted from February to May 2025 at the Unram Farming experimental field located in Nyurlembang Village, West Lombok, which was arranged according to Split Plot design, with three blocks and two treatment factors, namely weed species as bacteria sources (L1: Arachis pintoi, L2: Mimosa pudica, L3: Clitoria ternatea, L4: their mixture) as the main plots, and the types of bacteria (M0: without bacteria (autoclave sterilized bacterial isolates), M1: root nodule bacteria, M2: rhizosphere bacteria, M3: combination of both bacteria) as subplots. Observations were made on five sample clumps per treatment to measure growth, yield and yield components. Data were analyzed with ANOVA and Tukey's HSD at 5% significance level using CoStat for Windows. The results showed that application of rhizosphere and nodule bacteria significantly increased growth, yield, and yield components of mungbean, including branch number, nodule number, pod number, and grain yield per clump, with the best treatment being the combination of both types of bacteria isolated from A. pintoi, with the highest grain yield of 8.68 g/clump compared with 5.54 g/clump if without bacteria application. This indicates that these bacteria can potentially be developed as a local biofertilizer to support mungbean production in irrigated rice fields.